Auditory exostosis: Exploring the daily life at an early sedentary population (Körtik Tepe, Turkey). (28th May 2018) - Koruyucu, M. M.; Şahin, F. S.; Delibaş, D.; Erdal, Ö. D.; Benz, M.; Özkaya, V.; Erdal, Y. S.
Abstract: Auditory exostosis (AE) is a bony anomaly located on the tympanic portion of the temporal bone. Cold water, wind chill, and the effects of temperature are considered to be contributors to the development of AE. It is frequently encountered among surfers, lifeguards, whitewater kayakers, swimmers, and divers. Accordingly, there is a strong relationship between prolonged exposure to cold water and the frequency and grade of AE. For this reason, AE can be accepted as an occupational anomaly. In this study, AE from Körtik Tepe, Turkey, were analysed to understand the lifestyle of early hunter gatherer populations from Anatolia. One hundred twenty‐eight individuals and 174 temporal bones from Körtik Tepe were examined for the frequency and severity (graded) of AE. Forty‐five individuals (35.2%) have exostosis of various sizes. Half of 40 male individuals and 42.5% of females ( n : 40) have AE with no statistically significant difference between the sexes. First observed in individuals 7 years of age, severity and frequency of AE increase with age. Besides increasing in frequency, the increase in size of AE suggest a continuous and prolonged exposure to cold water. The people of Körtik Tepe, which is surrounded by numerous freshwater sources, must have been subjected to cold water through activities such as bathing, cleaning, swimming, and playing in the water, as well as fishing. Our results suggest that the lifestyle of early sedentary people in Körtik Tepe was rather egalitarian with little or no gender differences and was closely connected to aquatic sources. Bioarchaeological data suggest that Körtik Tepe can be accepted as a community of hunter‐gatherer‐fishermen.